Analysis of the Implementation of Social Entrepreneurship Management for the Sustainability of Orphanages - Teresia Soeprihatin; Erny Tajib (Green Publisher Indonesia, 2025)
Children orphanage is defined as a non-profit social organization with the responsibilities of caring, fostering and educating abandoned and orphaned children, which is funded by the society’s incidental donation. An orphanage requires a lange amount of funding to provide for the children’s needs and its operational costs, for which relying sosely on donation does not suffice. The most suitable solution is to run a social entrepreneurship management to gain income. This research is amined at analyzing the implementation of social entrepreneurship management for the sustainability of the orphanage, in terms of the benefits and challenges, the strategies to overcome the challenges, and its relation the SDGs and ISO 26 000. The objects of the research are the proprietorships at Abhimata Orphanage and Santa Maria Ganjuran Orphanage. This research is qualitative descriptive, untilizing the data collection technique, content analysis and triangulation for data amalysis, with the descriptive statistic analysis and qualitative data analysis. Results hane shown that the management implemented in the orphanages’ social entrepreneurship has brought about positive impacts on the orphanages, although the income obtained does not entirely fulfil their needs. Apart from that, the orphanages’ social entrepreneurship has contributed to the national purpose of creating the welfare of the society, as stated in the SDGs and ISO 26 000.